The Effect of Early Range of Motion Exercises on Pain Relief After Total Knee Replacement Postoperatively Versus Patients Advised Knee Immobilization; A Comparative Study - Imran Manzoor, Rizwan Khan Lodhi, Imanullah Riaz, M. Mujeeb Ur Rehman, Muhammad Ahmed, Muhammad Waseem (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Objective: The study aims to assess the effect of early range of motion exercises on pain relief after total knee replacement post operatively as compared to patients who are advised knee immobilisation post operatively